The Role of Cathepsin B in Peritoneal Fibrosis due to Peritoneal Dialysis - Su Ah Sung; Dong Hee Kim; Kook-Hwan Oh; Sang Youb Han; Kum Hyun Han (International Journal of Nephrology)
Glucose-containing peritoneal dialysis (PD) solution causes peritoneal fibrosis (PF) characterized by accumulation of extracellular matrix (ECM) in the submesothelial layer. Cathepsin B is a lysosomal cysteine protease that degrades ECM, but its role in the PF remains unclear. Thus, we investigated the role of cathepsin B in PF. Procathepsin B was measured in the 73 PD effluents of 68 patients. Procathepsin B and cathepsin B after exposure of glucose and the effects of cathepsin B on the expression of matrix metalloproteinases (MMPs), tissue inhibitor of metalloproteinases (TIMPs), and urokinase-type plasminogen activator (uPA) were measured in the supernatant of cultured human peritoneal mesothelial cells (HPMCs). The effect of cathepsin B and its inhibitor, cystatin C, on PF was investigated in the murine model. Procathepsin B was measured at 3.6 μg/L in serum and 5.4 μg/L in PD effluent and positively correlated to the cancer antigen (CA) 125. The treatment with 4.25% glucose increased procathepsin B by 3.1-fold and cathepsin B by 5.9-fold in the HPMCs. Cathepsin B induced the secretion of MMP-1, -2, and -3 and TIMP-1 in the HPMCs, but uPA was not excreted. In the PF murine models, cathepsin B reduced the thickness of the submesothelial layer and cystatin C attenuated the effect of cathepsin B. HPMCs secrete cathepsin B with exposure of PD solution, and cathepsin B might help protect against PF.